Polyamines deficient diet is a complementary strategy in fighting cancer: an investigation on selected medicinal fruits - Abdul Ghani, Radiah; Jamil, Elyna Fatini; Mohd. Sajungi, Nur Hikmah; Aznan, Azni Masturah (2017)
Polyamines are one of the oldest substances known in biochemistry consist of putrescine, spermidine and spermine. They are essential components of all living cells primarily involve in cell growth and proliferation. Mammalian cells are able to synthesize polyamines but are predominantly acquire them from exogenous sources such as intestinal flora and diets. However, the dietary sources provide a larger quantity of polyamines than the endogenous biosynthesis. Polyamines are tightly regulated by systematic biosynthesis and catabolism. Dysregulation of this system is highly associated with various diseases, including cancer. Therefore, polyamines deficient has become one of the strategies to inhibit carcinogenesis by targeting each biosynthetic and catabolic step in polyamines metabolism. Polyamine deficient diet (PDD) is a part of nutritional cancer therapy that recommends foods with low polyamines intake by cancer survivor and patients. In some cases, the plants might show anticancer effect but since the polyamines is high, it should not recommend for patients to avoid recurrence of cancer. Thus, this study was aimed to determine the polyamines content in selected anticancer fruits and plants in Malaysia and the effect on polyamine biosynthetic and catabolic enzymes was explored using human lung carcinoma cells (A549) as in vitro model.